Impact of the Covid-19 Pandemic on Bali’s and Indonesia’s Economic Growth - Antara, Made; Sri Sumarniasih, Made (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 16 No 2 (2022): Vol 16 No 2 (2022)DO - 10.24843/SOCA.2022.v16.i02.p06, 2022)
The Covid-19 pandemic that broke out in 2020, caused foreign tourist visits to Bali and Indonesia to decrease drastically. Sectors related to tourist arrivals such as various service sectors, agriculture and small and mediumsized industries experienced a decline in demand, followed by a decrease in added value for sectors related to tourism. The purpose of the study is to analyze the impact of the Covid-19 pandemic on the economy of Bali and Indonesia. The research locations are in the Provinces of Bali and Indonesia, using secondary data source from BPS Bali and BPS RI. The data analysis method used descriptive statistics, comparison methods before and after the Covid19 pandemic, and qualitative descriptive. The results of the research was found that impact of the COVID-19 pandemic in 2020 causing the Balinese economy to contract as deep as -9.31% compared to Bali economic growth 2019. The impact of the Covid-19 pandemic on the Indonesian economy, decreased Indonesia's economic growth in 2020 only contracted -2.07% compared to 2019. The novelty of this research is that the Covid-19 pandemic has an impact on reducing Bali and Indonesia economic growth, but the decline of Bali economic growth is more severe than Indonesia economic growth.